2014
DOI: 10.1007/s13187-014-0705-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Cancer Fear: The Association Between Mass Media and Fear of Cancer Among Cancer Diagnosed and Nondiagnosed Individuals

Abstract: Few studies have explored the impact of mass media on fear of cancer levels. This study investigates whether television and Internet use are associated with fear of cancer, and whether this association is different for cancer diagnosed and nondiagnosed individuals. A quantitative, standardized survey was used and administered to 2008 respondents in Flanders (Belgium), of which 621 individuals were diagnosed with cancer. For statistical analyses, hierarchical regression analyses, independent samples T-tests and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…The effect of media sources was seen to be a function of exposure, but not valence. The exposure result is consistent with many studies . On the other hand, the valence of mediated messages about Zika did not significantly predict fear in our data, despite the fact that a small literature shows just such an influence .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The effect of media sources was seen to be a function of exposure, but not valence. The exposure result is consistent with many studies . On the other hand, the valence of mediated messages about Zika did not significantly predict fear in our data, despite the fact that a small literature shows just such an influence .…”
Section: Discussionsupporting
confidence: 92%
“…For instance, a meta‐analysis of cultivation research reported that frequency of exposure to television is positively associated with perception of real‐world violence . Other work indicates a direct relationship between media exposure and health‐related risk estimation and between exposure and fear of cancer and fear of terrorism . Shrum offers a cognitive explanation for such effects when he asserts that frequency of activation is sufficient to enhance the accessibility of constructs in memory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for amplification, frequency of exposure via newspapers/magazines showed the anticipated positive association with fear. This result echoes findings from many previous studies that reported an influence of media exposure on risk (e.g., Coleman, 1993;Young et al, 2008) but joins a relatively small number of investigations that found a parallel effect on fear (Nelissen et al, 2015;Silver et al, 2013). Interpersonal communication also showed positive relationships such that more frequent exposure to Ebola-related communication led to higher levels of fear of Ebola.…”
Section: Media and Interpersonal Predictors Of Fearsupporting
confidence: 87%
“…For instance, a meta-analysis of cultivation research reported that frequency of exposure to television is positively associated with perception of real-world violence (Morgan & Shanahan, 1997). Other work has indicated a positive relationship between media exposure and health-related risk estimation (Coleman, 1993;Morton & Duck, 2001), perceived disease severity (Young, Norman, & Humphreys, 2008), fear of cancer (Nelissen et al, 2015), and fear of terrorism (Nellis & Savage, 2012;Silver et al, 2013). Shrum (2008) offered a cognitive explanation for such effects when he asserted that frequency of activation is sufficient to enhance the accessibility of constructs in memory.…”
Section: Media and Interpersonal Predictors Of Fearmentioning
confidence: 99%
“…In contrast, people seeking information about cancer primarly through television and the Internet could have a more negative perception of health, and this perception might be associated with a greater fear of cancer. To help reduce the burden of cancer worry, educators and health professionals must be aware of the possible negative effects that the news media can sometimes have ( 26 ). Furthermore, the fear of receiving bad news about health can cause people to avoid searching for information that might well be crucial for maintaining health.…”
Section: Discussionmentioning
confidence: 99%